2022
DOI: 10.1007/s00603-021-02743-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Least Principal Stress in a Granitic Rock Mass: Systematic Mini-Frac Tests and Elaborated Pressure Transient Analysis

Abstract: The hydraulic fracturing technique (also termed mini-frac test) is commonly used to estimate the in situ stress field. We recently conducted a mini-frac stress measurement campaign in the newly-established Bedretto Underground Laboratory (BedrettoLab) in the Swiss Alps. Four vertical boreholes, dedicated for stress characterization of the granitic rock mass, hosted a total of 19 mini-frac test intervals. Systematic pressure transient analysis was performed to carefully estimate the magnitude of the least princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 77 publications
(121 reference statements)
1
17
0
Order By: Relevance
“…Using acoustic televiewer logs (Figures 2b–2d), we chose the three adjacent sections containing pre‐existing natural fractures intersecting the SB 1.1 borehole. Besides the natural fractures, no stress‐induced borehole damage, such as borehole breakouts or drilling induced tensile fractures were expected (Bröker & Ma, 2022) or observed in the selected intervals. The final lengths of the isolated intervals between packers were 0.44, 1.94, and 1.01 m for Intervals 2, 3, and 4, respectively (Figure 2a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using acoustic televiewer logs (Figures 2b–2d), we chose the three adjacent sections containing pre‐existing natural fractures intersecting the SB 1.1 borehole. Besides the natural fractures, no stress‐induced borehole damage, such as borehole breakouts or drilling induced tensile fractures were expected (Bröker & Ma, 2022) or observed in the selected intervals. The final lengths of the isolated intervals between packers were 0.44, 1.94, and 1.01 m for Intervals 2, 3, and 4, respectively (Figure 2a).…”
Section: Methodsmentioning
confidence: 99%
“…We performed 175 PHT experiments in Interval 3 over a period of 5 months, during which the testing system remained at a fixed position. During the campaign, we considered (a) two different injection protocols, namely harmonic or sinusoidal‐wave‐type injection (Figure 3a) and non‐harmonic or square‐wave‐type production (Figure 3b) of fluid; (b) oscillation periods T from 7.5 to 1,800 s, that is, covering around 3 orders‐of‐magnitude; (c) a range of sufficiently small flow rates to ensure that the mean interval pressure remained below the expected fracture reopening pressures (Bröker & Ma, 2022); and (d) complementary conventional testing. The summary of parameters employed and dates of the testing campaigns are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The considered borehole, referred to as SB1.1, is 28.6 m deep and penetrates several pre-existing natural fractures, which have been identified by acoustic televiewer (ATV) logging. The selected borehole was used for a hydraulic stimulation experiment to characterize the in situ stress by measuring the formation breakdown, fracture closure, and fracture reopening pressures (Bröker & Ma, 2022). This resulted in the creation of several new small fractures.…”
Section: Experimental Settingmentioning
confidence: 99%
“…However, a number of theoretical analyses and experiments demonstrated that the plane of hydraulic fracture propagation is orthogonal to the minimum principal stress (Harrison et al., 1954; Hubbert & Willis, 1957). Based on this notion, hydraulic fracturing has become an established means to estimate the minimum principal stress as the fracture planes open against the minimum principal stress (Abou‐Sayed et al., 1978; Baumgärtner & Zoback, 1989; Haimson & Fairhurst, 1969) or even the intermediate principal stress (Schmitt & Zoback, 1989), though debates on pressure interpretation are yet to be settled (Bröker & Ma, 2022; F. Guo et al., 1993; Jung et al., 2016; Kamali & Ghassemi, 2019). A thorough review on this subject is provided by Schmitt and Haimson (2017).…”
Section: Introductionmentioning
confidence: 99%